2016
DOI: 10.1080/09687637.2016.1178708
|View full text |Cite
|
Sign up to set email alerts
|

“Skittles & Red Bull is my favourite flavour”: E-cigarettes, smoking, vaping and the changing landscape of nicotine consumption amongst British teenagers – implications for the normalisation debate

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 32 publications
8
55
0
Order By: Relevance
“…As Measham et al . (: 234) note, we are forced to interrogate our existing understanding of what it is that is being disapproved of in smoking and vaping, and ask: ‘to what extent does cultural acceptability or condemnation hinge on being able to see or smell consumption in public places?’. As Fairchild et al (: 295) point out, with reference to first generation ‘cigalikes’: ‘from the glowing tip to the smoke like vapour, e‐cigarettes seek to mimic the personal experience and public performance of smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Measham et al . (: 234) note, we are forced to interrogate our existing understanding of what it is that is being disapproved of in smoking and vaping, and ask: ‘to what extent does cultural acceptability or condemnation hinge on being able to see or smell consumption in public places?’. As Fairchild et al (: 295) point out, with reference to first generation ‘cigalikes’: ‘from the glowing tip to the smoke like vapour, e‐cigarettes seek to mimic the personal experience and public performance of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting the idea that e‐cigarettes are a distinct product and vaping a distinct activity from smoking and so not a route for smoking renormalisation, Measham et al . (), used participatory methods with a large sample of UK teenagers, and found that e‐cigarette use was initiated for the desirable flavours and the novelty of the products. Drawing on small groups discussions in the US, Roditis and Halpern‐Felsher (), proposed that lack of knowledge about e‐cigarettes led teenagers to have more positive opinions about the devices.…”
Section: E‐cigarettesmentioning
confidence: 99%
“…Miech at colleagues (Miech, Patrick, O'malley, & Johnston, 2016) have shown that the consumption of non-nicotine containing flavoured e-liquids was actually more common than the use of nicotine containing e-liquids. Similarly, Measham and colleagues (Measham, Obrien, & Turnbull, 2016) have shown that many of the young people in their qualitative research were more interested in the theatricality of being able to create large plumes of exhaled vapour than in meeting their need to consume nicotine (Measham et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Contributions to the special issue come from the UK, Canada and Australia and explore what stable and declining drug use rates among young people mean for normalisation (Williams, 2016) and whether a denormalisation, or renormalisation, of some substance use has occurred, particularly with respect to tobacco and nicotine (Asbridge, Valleriani, Kwok, & Erickson, 2016;Measham, O'Brien, & Turnbull, 2016). Important criminal justice issues such as the normalisation of the social supply of illicit drugs (Coomber, Moyle, & South, 2016) and the incongruence between cannabis policy and community attitudes to cannabis (Asbridge et al, 2016) are explored.…”
Section: Editorialmentioning
confidence: 99%
“…Important criminal justice issues such as the normalisation of the social supply of illicit drugs (Coomber, Moyle, & South, 2016) and the incongruence between cannabis policy and community attitudes to cannabis (Asbridge et al, 2016) are explored. Papers also focus on somewhat neglected aspects of normalisation such as gender and ethnicity (Hathaway, Mostaghim, Kolar, Erickson, & Osborne, 2016), socioeconomic status and broader structural factors shaping drug use (O'Gorman, 2016), age and intimate relationships (Green, 2016), the importance of social context (Asbridge et al, 2016;Hathaway et al, 2016) and routes of ingestion (Measham et al, 2016) in understanding processes of normalisation.…”
Section: Editorialmentioning
confidence: 99%